The features of the commercialization of innovations in some countries - Mamrayeva, D.G.; Tashenova, L.V. (Вестник Карагандинского университета, 2016)
In the article the features of the commercialization of innovation systems in countries with successful experi- ences of measures by the promoting and supporting the industrial innovation system were investigated. In particular, the experience of Finland, Germany, Japan, China, the United States and other countries was shown. On the basis of world experience highlighted a wide range of innovation support in these countries, including government programs of financial and technical support to innovative companies that perform re- search and development work on the subject of government agencies; direct funding, which reaches about 50 % in the creation of new products and technology costs; granting of loans, including without payment of interest; grants to cover 50 % of the costs for the implementation of innovations; targeted subsidies for re- search and development; the creation of innovation are assets in view of possible commercial risk; reduction in government fees for individual inventors and the presentation of their tax benefits, as well as the creation of special infrastructure to support them, and economic security; free services of patent attorneys at the re- quest of individual inventors, exemption from payment of fees; tax relief for companies operating in the sphere of innovation; legislative support for intellectual property rights and copyright; government programs to reduce risks and risk compensation of losses; creation of a network of science parks, business incubators and technological development zones; information retrieval specialized sites on advanced technologies and innovative developments, allowing interested companies to quickly find the needed technical solutions and potential partners.
Keywords: innovation activity; global experience in the commercialization of innovations; innovative enterprise; innovative development; the venture capital industry